Kesantunan Mengkritik Bossman Mardigu Di Acara Youtube - Ismail; Siti Ainim Liusti (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2023)
This study aims to describe (1) the politeness principles used by Bossman Mardigu on the YouTube show, (2) the language politeness strategies used by Bossman Mandigu. The research data are in the form of words, phrases, clauses, and sentences related to politeness criticizing Bossman Mardigu on the YouTube program. The data collection techniques used in this study are as follows: (1) Download videos of the Bossman Mardigu podcast via YouTube. (2) listening to Bossman Mardigu's podcast and transcribing the data into written form, (3) inventorying the data into an inventory format. The validation technique in this study uses a triangulation technique. Furthermore, data analysis in this study was carried out with the following work steps: (1) grouping data in the form of polite speeches criticizing Bossman Mardigu on YouTube; (2) analyzing data that has been grouped through the data classification stage; (3) interpreting the data found; and (4) summarizing the data and writing reports or analyses that have been carried out. There are two findings in this research. First found as many as six violations of the principle of politeness. Secondly, there were five speech strategies used by Bossman Mardigu. Based on the research findings, it can be concluded that Bossman Mardigu violates the principle of politeness more when criticizing, or can be said to be impolite.